2020
DOI: 10.1016/j.fertnstert.2019.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial thickness is associated with incidence of small-for-gestational-age infants in fresh in vitro fertilization–intracytoplasmic sperm injection and embryo transfer cycles

Abstract: Objective: To investigate whether endometrial thickness (EMT) is associated with adverse obstetric and neonatal outcomes in fresh in vitro fertilization/intracytoplasmic sperm injection-embryo transfer (IVF/ICSI-ET) cycles. Design: Retrospective cohort study. Setting: University-based reproductive medical center. Patient(s): Women under the age of 42 years who underwent IVF/ICSI treatment and received fresh ET in our unit from January 2017 to December 2018, resulting in a live singleton birth. Intervention(s):… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 41 publications
2
65
1
Order By: Relevance
“…Guo et al studied EMT on the day of hCG detection in fresh-embryo transfer cycles. They found insu cient EMT to be a risk factor for neonatal SGA [11]. Thus, in accordance with our results, newborns with a thinner endometrium had a lower weight and an increased risk of SGA.…”
Section: Discussionsupporting
confidence: 92%
“…Guo et al studied EMT on the day of hCG detection in fresh-embryo transfer cycles. They found insu cient EMT to be a risk factor for neonatal SGA [11]. Thus, in accordance with our results, newborns with a thinner endometrium had a lower weight and an increased risk of SGA.…”
Section: Discussionsupporting
confidence: 92%
“…All patients were given a conventional ovarian stimulation regimen, and TVU was used to monitor the growth and development of follicles. Different ovarian stimulation protocols were selected according to the patient's age and ovarian function, including gonadotrophin-releasing hormone (GnRH) agonist long protocols, GnRH agonist short protocols, flexible GnRH antagonist protocols, mild stimulation protocols, and natural cycle protocols, which have been previously reported (10). Next, hCG was given intramuscularly at a dose of 4,000-10,000 IU when two or more follicles measured ≥18 mm.…”
Section: Ivfmentioning
confidence: 99%
“…In an analysis of over 6,000 singleton newborns, Zhang et al (26) found that among women undergoing day 3 frozen embryo transfer, an endometrial thickness of <8 mm was significantly associated with lower birth weight compared with an endometrial thickness of R10 mm after adjusting for gestational age. In addition, Guo et al (27) found that endometrial thickness was significantly associated with birth weight and those with an endometrial thickness of %7.5 mm were significantly more likely to have a small-for-gestational-age neonate compared with to those with an endometrial thickness of >12 mm. Taken together, these studies indicate that endometrial thickness is a significant factor in healthy pregnancy and fetal development and support using a goal endometrial thickness of R7 mm as a conservative cutoff for progressing with embryo transfer.…”
Section: Discussionmentioning
confidence: 99%